REKAYASA ULANG PROSES BISNIS PADA SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) TINGKAT KECAMATAN (STUDI KASUS : KECAMATAN KARTASURA) - Setiyowati Setiyowati; Sri Siswanti (STMIK Sinar Nusantara, 2016)
Sistem Informasi Administrasi Kependudukan (SIAK) is an information system that is built to support the administrative process that includes registration of resident population and civil registration. With this system a national population database will be realized gradually. SIAK in the application of Technical Implementation Unit (UPTD) in the district level there are procedures that must be followed by the people who will carry out the transaction for example moving the population administration, changes in demographic data, KK, ID cards and others. The process of registration of participants beginning data collection that starts from the village there is no facility applications that handle these transactions, data from villages not connected to the existing data in the district. Business process reengineering residence registration reduces existing processes so that more efficiently. Keywords: Business process reengineering, information system.